Impact of Cochlear Nerve Deficiency Determined Using 3-Dimensional Magnetic Resonance Imaging on Hearing Outcome in Children with Cochlear Implants. Issue 1 (January 2015) - Wu, Che-Ming; Lee, Li-Ang; Chen, Chin-Kuo; Chan, Kai-Chieh; Tsou, Yung-Ting; Ng, Shu-Hang
Abstract : Objectives: 1) To review the radiologic and audiologic data of 656 children with sensorineural hearing impairment who underwent 3-dimensional magnetic resonance imaging (MRI) in our cochlear implant (CI) center to understand the incidence of cochlear nerve deficiency (CND); and 2) to compare postimplant auditory and speech intelligibility outcomes in implantees with cochlear nerve (CN) aplasia, CN hypoplasia, and normal CN. Study Design: A retrospective cohort study. Setting: A tertiary medical center. Patients: A total of 656 patients (aged 0–18 yr; mean, 4.5 ± 4.3 yr) who underwent MRI in our center during May 2000 to December 2012. Main Outcome Measures: The radiologic/audiologic data were reviewed. The postimplant outcomes of 13 implantees with CND (7 aplasia and 6 hypoplasia) were compared with 50 non-CND implantees using the Categories of Auditory Performance (CAP) and the Speech Intelligibility Rating (SIR) scales. Results: Upon MRI, 139 patients (21.2%) exhibited CND. Bilateral CN aplasia occurred in 4.3% of the patients with severe-to-profound deafness (588 cases) and in one-fifth of patients with CND. The aplasia group showed significantly worse postimplant CAP ( p = 0.002) and SIR ( p = 0.009) scores than the non-CND group. No significant difference was noted between the hypoplasia group and the non-CND group. Conclusion: Although the audiologic and radiologic results may be incompatible, the majority of patients with CND may be well delineated preoperatively using MRI. The type of CND (aplasia/hypoplasia) may affect CI outcomes. Patients implanted on the side with CN hypoplasia are more likely to exhibit favorable results compared with patients implanted on the side with CN aplasia.